Analysis of Site Selection Criteria for Design of Paddy Research Facilities in Nganjuk Regency - Thomafi, Muhamad Arvan; Muhammad Faisal; Darmansjah Tjahja Prakasa (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
Nganjuk Regency in East Java is one of the contributors to rice production in Indonesia, where agricultural land areas are more dominant than non-agricultural land areas. However, this sector faces major challenges including declining production due to internal and external factors such as climate change, limited infrastructure, and less than optimal use of modern agricultural technology. This study aims to analyze the criteria for selecting a location for designing a paddy research facility in Nganjuk Regency to support sustainable production increases. The methodology used includes analysis of regional potential based on statistical data on agricultural production, agro-climatic conditions, and topography. The survey results show that although rice production in this area reached 418.10 tons in 2023 and became one of the contributors to the rice harvest in East Java Province, intensive research and infrastructure development have not been carried out. The main criteria for selecting a location include proximity to water resources and ease of land access, suitability with regional spatial planning, and potential with other agricultural research centers. The design of this facility aims to be an integrated solution not only to increase the production and quality of high-quality seed varieties, but also to support scientific research and cutting-edge technology in the agricultural sector. By integrating technology-based approaches and local potential, this facility can become a model for sustainable agricultural development in Nganjuk Regency.